Sexual Activity before Competition and Athletic Performance: A Systematic Review - Mohsen Soori; Shahram Mohaghegh; Maryam Hajian; Amirhossein Abedi Yekta (The Society of Aging and Physical Activity (SAPA), 2017)
Objectives. The purpose of the present study was to systematically evaluate the scientific evidence about the impact of pre-competition sexual activity on athletic performance. Methods. Using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement, PubMed, Scopus, ISI Web of Science, Cochrane Library, ProQuest, Physiotherapy Evidence Database(PEDro), and Google Scholar searches were performed with appropriate keywords without time and language restrictions for studies evaluating the impact of sexual activity on athletic performance. The titles and abstracts were reviewed by two independent reviewers. The methodological quality of the studies and the risk of bias were checked using the quality assessment tool of the Critical Appraisal Skills Program (CASP). Results. We found that most studies on this topic had low methodological quality. Out of the456 articles retrieved in the search, only seven met the inclusion criteria of the review. In four of these studies, sexual activity10-12 hours before competition did not alter short-term physiological testing results including maximum-effort grip strength test, hamstring flexibility, reaction time, aerobic power (stair-climbing exercise), VO2max (treadmill and cycle ergometer test), sub-maximal graded-exercise test, muscular endurance, oxygen pulse, double product, testosterone, cortisol, blood glucose concentrations, and mental concentration. In one study, significantly higher differences were reported for post-maximal stress test heart rate at 5 and 10 minutes during two hours of recovery period after sexual intercourse, which disappeared when a maximal stress test was performed 10 hours after sexual activity. In another study immediately after sexual intercourse, 40% of long-distance athletes had difficulty during intensive loading, while in 90% of the addressed athletes, sexual activity 12 hours before the endurance test did not have an influence on performance. Conclusion. Based on mainly low-quality and heterogeneously designed studies, it can be concluded that having sex at least 10-12 hours before athletic events does not negatively influence physiological test results and possibly athletic performance. However, having sex immediately or a few hours before a competition has negative psychological or physiological effects on athletic performance.